Effects of crustal field rotation on the solar wind plasma interaction with Mars. Issue 19 (1st October 2014) - Ma, Yingjuan; Fang, Xiaohua; Russell, Christopher T.; Nagy, Andrew F.; Toth, Gabor; Luhmann, Janet G.; Brain, Dave A.; Dong, Chuanfei
Abstract The crustal remnant field on Mars rotates with the planet at a period of 24 h 37 min, constantly varying the magnetic field configuration interacting with the solar wind. Until now, there has been no self‐consistent modeling investigation on how this varying magnetic field affects the solar wind plasma interaction. Here we include the rotation of this localized crustal field in a multispecies single‐fluid MHD model of Mars and simulate an entire day of solar wind interaction under normal solar wind conditions. The MHD model results are compared with Mars Global Surveyor (MGS) magnetic field observations and show very close agreement, especially for the field strength along almost all of the 12 orbits on the day simulated. Model results also show that the ion escape rates slowly vary with rotation, generally anticorrelating with the strength of subsolar magnetic crustal sources, with some time delay. In addition, it is found that in the intense crustal field regions, the densities of heavy ion components enhance significantly along the MGS orbit, implying strong influence of the crustal field on the ionospheric structures.